Daya Hambat Ekstrak Metanol Daun Sukun (Artocarpus communis Forst) terhadap Pertumbuhan Bakteri Pseudomonas aeruginosa dan Staphylococcus aureus Penyebab Infeksi pada Luka - Muharram; Ramdani; Eviyusmiawati Sius (Jurusan Biologi Universitas Negeri Makassar, 2008)
This research is aimed to know the inhibiting capacity of methanol extact of Artocarpus communis Forst leaves to bacteria that causing infection on wound, i.e. P. aeruginosa and S. Aureus. Therefore, the sensitivity of both bacteria must be examined to methanol extract of Artocarpus communis Forst leaves. The sensitivity test was condsucted by paper disc method. The inhibition zone of methanol extract of Artocarpus communis Forst leaves was founded as a colourless zone that obtained after incubation for 24 hours. It is means P. aeruginosa and S. Aureus are sensitive to methanol extract of this plant. The inhibition zone is shown by methanol extract of Artocarpus communis Forst leaves toward bacteria coloni growth of P. aeruginosa and S. aureus that describingthe linear increasing of consentration from 5% to 20%. It is shown that Artocarpus communis Forst leaves contains the activity compounds as antibacteria, especially P. aeruginosa and S. aureus.